2005
DOI: 10.1007/s10725-005-8647-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the ipt Gene with the AGPase S1 Promoter in Tomato Results in Unbranched Roots and Delayed Leaf Senescence

Abstract: Transgenic tomato plants were produced with the isopentenyl transferase gene (ipt) ligated to a promoter that is active exclusively in sink tissue. Initially, transgenic plants had smaller, round-scale leaves, swollen stems, and exhibited early development of lateral shoots compared to wild type. Expression of the ipt gene resulted in the formation of unbranched roots on cuttings and delayed senescence in excised leaves. Callus and root formation occurred on excised leaves and leaf discs during dark incubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…It has been previously reported that the elevated cytokinin production in ipt-transgenic plants often resulted in the release of apical dominance, in the form of excessive lateral branching or flower buds in many dicot plant species (Clark et al 2004;Khodakovskaya et al 2006), and in the form of increased tillering ability in tall fescue grass (Hu et al 2005). Many other studies reported decreased root branching after stress treatment in ipt-transgenic dicot plants (Clark et al 2004;Luo et al 2005), and severe reductions in root growth in plants transformed with ipt driven by constitutive promoters (Hewelt et al 1994;Van Loven et al 1993). In contrast, most of the transgenic creeping bentgrass with the senescence-inducible promoter produced more roots, and had greater total root length than the control line under both normal growth temperature and heat stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that the elevated cytokinin production in ipt-transgenic plants often resulted in the release of apical dominance, in the form of excessive lateral branching or flower buds in many dicot plant species (Clark et al 2004;Khodakovskaya et al 2006), and in the form of increased tillering ability in tall fescue grass (Hu et al 2005). Many other studies reported decreased root branching after stress treatment in ipt-transgenic dicot plants (Clark et al 2004;Luo et al 2005), and severe reductions in root growth in plants transformed with ipt driven by constitutive promoters (Hewelt et al 1994;Van Loven et al 1993). In contrast, most of the transgenic creeping bentgrass with the senescence-inducible promoter produced more roots, and had greater total root length than the control line under both normal growth temperature and heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Different morphological and physiological changes have been observed in individual ipt transgenic plants due to the overproduction of cytokinins. Luo et al (2005) reported that expression of the ipt gene ligated to the AGPase S1 promoter, which is active exclusively in sink tissues in tomato (Lycopersicon esculentum L.), resulted in the retention of chlorophyll and cytokinin in excised leaves or discs, as well as the greater formation of unbranched roots on cuttings compared to the wild type. In transgenic ipt tobacco plants under the control of a promoter for the small subunit of RuBPCO (Pssu-ipt), overproduction of endogenous cytokinins caused stress responses such as overaccumulation of phenolic compounds, synthesis of pathogenesis related proteins and increase in peroxidase activities (Schnablova et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…5). Expression of IPT under the AGPase S1 promoter in tomato plants also resulted in delayed senescence of detached leaves (Luo et al, 2005). Yet, Chen et al (2001) found that in detached leaves and florets of broccoli only P SAG13 ::IPT plants exhibited retardation of chlorophyll degradation.…”
Section: Discussionmentioning
confidence: 99%
“…This gene has been introduced into various plant species, mostly dicotyledonous plants, such as tobacco (Nicotiana tabacum) (Gan and Amasino, 1996), cauliflower (Brassica oleracea var. botrytis) (Nguyen et al, 1998), lettuce (Lactuca sativa) (McCabe et al, 1998;McCabe et al, 2001), arabidopsis (Arabidopsis thaliana) (Huynh et al, 2005), petunia (Petunia •hybrida) (Chang et al, 2003;Clark et al, 2004;Khodakovskaya et al, 2005), chrysanthemum (Dendranthema •grandiflorum) (Khodakovskaya et al, 2005), and tomato (Solanum lycopersicum) (Luo et al, 2005), and in a limited number of monocot plant species such as tall fescue (Festuca arundinacea) (Hu et al, 2005) and wheat (Triticum aestivum) (Sykorova et al, 2008). Most studies have confirmed that increases in endogenous production of CK delayed leaf senescence.…”
mentioning
confidence: 99%